2018
DOI: 10.1002/jcla.22671
|View full text |Cite
|
Sign up to set email alerts
|

Hb I: A α‐globin chain variant causing unexpected HbA1c results

Abstract: An unusually high HbA or discordance between blood sugar and HbA values should alert about the possibilities of hemoglobin variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An unusually low level of HbA1c or discordance between blood sugar and HbA1c values should alert clinicians to the possibility of Hb variants. Since the effect of a particular Hb variant on HbA1c results is frequently method-dependent (e.g., ion-exchange HPLC methods are frequently affected by the presence of Hb variants), repeat analysis should ideally be performed using an alternative method based on a different analytical principle from the initial assay ( 14 ); these alternative methods may include electrophoresis, immunoassays and enzymatic analysis. Among the methods, the principle of electrophoresis is based on the fact that colloidal particles with different electric charges under certain conditions move through an electric field by electrostatic attraction, which may identify abnormal Hb ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…An unusually low level of HbA1c or discordance between blood sugar and HbA1c values should alert clinicians to the possibility of Hb variants. Since the effect of a particular Hb variant on HbA1c results is frequently method-dependent (e.g., ion-exchange HPLC methods are frequently affected by the presence of Hb variants), repeat analysis should ideally be performed using an alternative method based on a different analytical principle from the initial assay ( 14 ); these alternative methods may include electrophoresis, immunoassays and enzymatic analysis. Among the methods, the principle of electrophoresis is based on the fact that colloidal particles with different electric charges under certain conditions move through an electric field by electrostatic attraction, which may identify abnormal Hb ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dessi et al showed that capillary electrophoresis analyzer is more suitable for HbA1c assay in hemoglobin variant samples compared to HPLC system (20). Xu et al observed that alpha globin chain variant caused unusually high HbA1c levels in a Chinese patient (21). One study showed that HbA1c levels were significantly low in patients with αthalassemia with one functional α-gene (Hb H disease) compared with controls (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used both boronate affinity and cation exchange HPLC systems as the reference when assessing HbA1c concentration 22,23 . The UK Biobank has used and certified the Variant™ II Turbo analyzer as the reference method for HbA1c measurement 24 .…”
Section: Methodsmentioning
confidence: 99%
“…7 Some studies used both boronate affinity and cation exchange HPLC systems as the reference when assessing HbA1c concentration. 22,23 The UK Biobank has used and certified the Variant™ II Turbo analyzer as the reference method for HbA1c measurement. 24 Since TMC Biobank uses the UK Biobank protocol as the reference standard, 17 we then change to Variant™ II Turbo analyzer for HbA1c analysis.…”
Section: Hba1c Measurementmentioning
confidence: 99%